2013
DOI: 10.1177/0009922813492881
|View full text |Cite
|
Sign up to set email alerts
|

Association of Screen Time Use and Language Development in Hispanic Toddlers

Abstract: This study examined the association between screen media use, media content, and language development among 119 Hispanic infants and toddlers. Children and their caregivers were recruited through an urban, Early Head Start program. Duration and content of screen media exposure was measured through a 24-hour recall questionnaire, and language development was measured at baseline and at 1-year follow up. Children in the sample spent an average of 3.29 hours engaged with screen media (median 2.5 hours per day). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
3
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 23 publications
5
100
3
18
Order By: Relevance
“…Of the 83 reported associations in 14 observational studies, between duration/frequency of childspecific TV content and cognitive development, nine (11%) were statically significant detrimental associations 33,41,42,50,52,56,58 and nine (11%) were statistically significant beneficial associations. 41,42,46,52,57 Three studies reported beneficial associations with cognitive development for some content (educational, ABC and PBS channel viewing), and detrimental associations for Figure 3 displays the number of statistically significant detrimental, statistically significant beneficial, and null associations between higher or increased child-specific TV content and cognitive development outcomes stratified by cognitive domain.…”
Section: Resultsmentioning
confidence: 98%
“…Of the 83 reported associations in 14 observational studies, between duration/frequency of childspecific TV content and cognitive development, nine (11%) were statically significant detrimental associations 33,41,42,50,52,56,58 and nine (11%) were statistically significant beneficial associations. 41,42,46,52,57 Three studies reported beneficial associations with cognitive development for some content (educational, ABC and PBS channel viewing), and detrimental associations for Figure 3 displays the number of statistically significant detrimental, statistically significant beneficial, and null associations between higher or increased child-specific TV content and cognitive development outcomes stratified by cognitive domain.…”
Section: Resultsmentioning
confidence: 98%
“…Population-based studies continue to show associations between excessive TV viewing in early childhood and cognitive, 54 -56 language, 57,58 and social/emotional delays. 59 -62 Possible mechanisms for these outcomes include the effects of viewing inappropriate, adult-oriented content 54 (as well as some inappropriate child-directed content), 58 a decrease in parent-child interaction when the TV is on, 63 and poorer family functioning in households with high media use.…”
Section: Health and Developmental Risks Of Media Use What Are The Devmentioning
confidence: 99%
“…59 -62 Possible mechanisms for these outcomes include the effects of viewing inappropriate, adult-oriented content 54 (as well as some inappropriate child-directed content), 58 a decrease in parent-child interaction when the TV is on, 63 and poorer family functioning in households with high media use. 60 An earlier age of media use onset, greater cumulative hours of media use, and content that is not of high quality all are significant independent predictors of poor executive functioning (impulse control, self-regulation, mental flexibility) 33 as well as "theory of mind" deficits (ie, the ability to understand others' thoughts and feelings) in preschoolers.…”
Section: Health and Developmental Risks Of Media Use What Are The Devmentioning
confidence: 99%
“…Population-based studies continue to show associations between excessive television viewing in early childhood and cognitive, 28 -30 language, 31,32 and social/emotional delays, 33 -36 likely secondary to decreases in parentchild interaction when the television is on 37 and poorer family functioning in households with high media use. 37 An earlier age of media use onset, greater cumulative hours of media use, and non-PBS content all are significant independent predictors of poor executive functioning in preschoolers.…”
Section: Child Developmentmentioning
confidence: 99%